2019
DOI: 10.1093/gji/ggz486
|View full text |Cite
|
Sign up to set email alerts
|

Using Bayesian model averaging to improve ground motion predictions

Abstract: SUMMARY In low-seismicity areas such as Europe, seismic records do not cover the whole range of variable configurations required for seismic hazard analysis. Usually, a set of empirical models established in such context (the Mediterranean Basin, northeast U.S.A., Japan, etc.) is considered through a logic-tree-based selection process. This approach is mainly based on the scientist’s expertise and ignores the uncertainty in model selection. One important and potential consequence of neglecting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…we have selected all the GMPEs in Bertin et al ( 2020)'s study except Derras et al (2016) from OpenQuake Engine library (Pagani et al, 2014) and tested their performance against ESM database. Similar to Bertin et al (2020)'s study, the three GMPEs (Bindi2011, Akkar2014, and Bindi2014) are dominant compared to other GMPEs over a set of periods against ESM database. Therefore, in this research, we present the results only for the dominant three GMPEs.…”
Section: Application: Gmpe Modelssupporting
confidence: 59%
See 3 more Smart Citations
“…we have selected all the GMPEs in Bertin et al ( 2020)'s study except Derras et al (2016) from OpenQuake Engine library (Pagani et al, 2014) and tested their performance against ESM database. Similar to Bertin et al (2020)'s study, the three GMPEs (Bindi2011, Akkar2014, and Bindi2014) are dominant compared to other GMPEs over a set of periods against ESM database. Therefore, in this research, we present the results only for the dominant three GMPEs.…”
Section: Application: Gmpe Modelssupporting
confidence: 59%
“…-Fixed parameter setting, f m (x) is fixed, with added bias term µ m and then estimate the weights. In Bertin et al (2020), fixed parameter setting with added bias term is considered.…”
Section: Stage 3: Model Updatingmentioning
confidence: 99%
See 2 more Smart Citations
“…A strong motion dataset that was considered to be representative of the expected ground motion on site was extracted from the RESORCE database, to challenge the predictions of the different GMPEs against these observed data. The SINAPS@ study clearly showed that without any a priori information on the GMPEs, the Bayesian model averaging provided hierarchy and weighting of the GMPEs that was only based on their relevance with respect to real data (Bertin et al 2019). This finally provided an objective ranking that avoided any expert advice that might be questionable (e.g., on the choice of the candidate GMPEs, on their weight in a logic-tree), as shown in Fig.…”
Section: Bayesian Tool As An Objective Alternativementioning
confidence: 94%